115 SMART: A rare syndrome with potentially devastating consequences. Issue 6 (27th May 2022) - Baheerathan, Aravindhan; Lynch, David; Pednekar, Nichil; Blindheim, Christer; Smyth, Ducan; Stockford, Lindsey; Rees, Jeremy
Abstract : Stroke like migraine attacks after radiation therapy (SMART) is an uncommon delayed complication after cranial irradiation. Whilst classically reported as a reversible syndrome, SMART can have serious neurologi- cal sequelae. We report three cases with differing neurological presentations and outcomes. A 57 year old female with previous cranial radiotherapy for a frontal astrocytoma treated 9 years earlier presented with a two week history of headache, aphasia and right sided hemiparesis. MRI Brain demon- strated new extensive left hemispheric enhancement with extensive effacement of the ipsilateral cerebral sulci. 40 days following her presentation she started to improve and is now in rehabilitation. A 33 year old female with a background of medulloblastoma treated with cranio-spinal radiotherapy 19 years earlier presented with worsening confusion. Her GCS continued to deteriorate and she was intubated and ventilated. MRI Brain showed extensive symmetrical signal anomalies with cortical enhancement along the occipital, temporal and parietal lobe borders. 2 months later she remains in a minimally conscious state. A 65 year old male with a background of acute lymphoblastic leukaemia treated 30 years earlier who was treated prophylactic cranial irradiation presented with headache and unintelligible speech. His symptoms settled after 7 days and he made an almost complete recovery. *Aravindhan Baheerathan and David Lynch are joint first authors c.c.blindheim@gmail.com